Struktur Modal dan Perputaran Kas terhadap Profitabilitas Bank BUMN dengan Kebijakan Dividen sebagai Variabel Intervening - Sari, Riana; Anggriani, Rini; Alpiansah, Restu; Hendri, Wira; Nirwana, Baiq Nadia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
State-Owned Enterprises (BUMN) banks have a crucial role in maintaining economic stability and growth. In addition to focusing on profit, these banks are also socially responsible in supporting infrastructure development, MSME development, and other programs. The purpose of this study was to determine the effect of capital structure and cash turnover on the profitability of state-owned banks with dividend policy as an intervening variable. The research conducted was a descriptive quantitative study with a causal approach. The researcher determined the number of samples at 45 by considering several criteria such as state-owned banks listed on the IDX for the 2014-2023 period, banks that published complete financial reports on the IDX for the 2014-2023 period, and banks that attached all variable data currently used by researchers for the 2014-2023 period. The data analysis tool used E-Views 12 software. The results of the study found that capital structure had no effect on profitability. Cash turnover had a negative and significant effect on profitability. Capital structure had a negative and significant effect on dividend policy. Cash turnover had a negative and significant effect on dividend policy. Dividend policy does not affect profitability. Based on the results of the test of the influence of intervening variables using the Sobel test, it shows that dividend policy is not able to mediate between capital structure and profitability. Dividend policy is not able to mediate cash turnover on profitability.